Exploring Factors Influencing Diabetes Mellitus Incidence Among Participants of Chronic Disease Management Program in Rural Areas - Alam, Syamsul; Wijaya, Dian Rezki; Kurniawan, Agil; Maesarah, Maesarah (Al-Sihah : The Public Health Science Journal, 2024)
Diabetes mellitus (DM) is a chronic disease with an increasing global prevalence, including in Gorontalo Province, specifically type 2 DM (T2DM). Various risk factors, such as lifestyle, obesity, and lack of physical activity have been reported to contribute to DM incidence. This shows the importance of developing more effective prevention and management strategies. Therefore, this study aimed to explore factors related to DM incidence among participants of Chronic Disease Management Program (Prolanis) in rural areas of Boalemo District, Gorontalo Province. A quantitative method was used with a cross-sectional approach on 300 participants who were selected through the purposive sampling method. Data were collected using questionnaires to measure physical activity, dietary patterns, and smoking habits. Meanwhile, body mass index (BMI) and blood glucose levels were measured anthropometrically and through blood sugar tests. The results showed that dietary patterns (carbohydrates (p=0.003), fats (p=0.00), and fiber (p=0.000)), smoking habits (p=0.016), BMI (p=0.039), age (p=0.00), genetic factors (p=0.00), and gender (p=0.00) were significantly associated with DM incidence, while physical activity (p=0.095) and protein intake (p=0.128) were not associated. In this context, dietary fiber intake was the strongest predictor with Odds Ratio (OR) value of 7.37. Based on the results, dietary fiber intake, smoking habits, BMI, and age had a significant influence as predictors of DM incidence. The implications for public health included the need to increase awareness of the importance of healthy dietary patterns, reduce smoking habits, and monitor BMI to control the prevalence and improve the overall welfare of rural community.